Tobacco use among Kola Sámi, the indigenous people of the Murmansk region, Russia: A cross-sectional study. Issue 1 (31st December 2022) - Merkin, Alexander; Akinfieva, Sofya; Nikolaev, Artem; Rocheva, Elena; Komarov, Alexander; Nikiforov, Igor; Glover, Marewa
ABSTRACT: Russia is among the top ten nations in terms of smoking prevalence. Little is known about smoking rates among Indigenous Peoples in Russia. Our aim was to assess the prevalence of tobacco and nicotine product use among Kola peninsula Sámi. An exploratory cross-sectional survey was conducted to determine tobacco or nicotine product use among 505 Sámi people (about 30% of the whole Sámi population of Russia). Over 60% of participants had tried tobacco or nicotine products. Median age of first use was 15 years, with cigarettes being the most frequent first product tried and the most common type of product used currently. About a third of participants used a tobacco or nicotine product at least occasionally; 25% (predominantly males) smoked at least occasionally with 23.8% smoking daily. Of participants who smoked, 52.5% scored medium and 44.2% scored high on the Heaviness of Smoking Index. Seventeen percent of participants smoked formerly but not currently. Like some other Indigenous Peoples, Kola Sámi in Russia have a higher smoking prevalence than the average among the Russian population. Interest in a smoking cessation mobile app designed for the Sámi population suggests that such an intervention could help to reduce this inequity.